The Effect of Increasing Surface Area of Graphite Electrode on the Performance of Dual Chamber Microbial Fuel Cells - Artsanti, Pedy; Sudarlin, Sudarlin; Kirana, Eka Fadzillah (Proceeding International Conference on Science and Engineering, 2017)
The effect of increasing surface area of graphite electrode on the performance of dual chamber Microbial Fuel Cells (MFC) was observed. The surface area of graphite electrode (anode and cathode) that was using in this experiment was 29.5cm2 and 44.5cm2 for the A and B reactor, respectively. The anode chamber contained mixed microorganism culture from real wastewater of textile industry and the cathode chamber contained 0.1M potassium permanganate electrolyte solution. The salt bridge was required to stabilize the charge between the anode and cathode chambers, and the electrodes attached to the anode and cathode chambers as the electron catcher. Both, the A and B reactor were observed for 72 hours of running time. The voltage and power density were found to increase with the increase in surface area of the graphite electrode. The highest power density was 93.93mWm-2 and 197.23mWm-2 that obtained at 36 hours and 48 hours on the A and B reactor, respectively. At the end of experiment, these MFCs system could also reduce COD by 28.6% and 15.6% on A and B reactor, respectively.